PEMBINAAN MODUL AMALI KURSUS PENYELENGGARAAN DAN PERKHIDMATAN BANGUNAN BAGI PROGRAM SARJANA MUDA PENDIDIKAN VOKASIONAL (BINAAN BANGUNAN) FPTV - Muhamad Hanafi, Nurfirdawati; Rozman, Nur Izati (Research and Innovation in Technical and Vocational Education and Training, 2023)
The Building Maintenance and Service Course is a new course introduced in the Bachelor of Vocational Education (Building Construction) program at the Faculty of Technical and Vocational Education. This course is delivered theoretically and practically. Therefore, based on the needs analysis study, it was found that there is a need to develop a practical module for this course. The objective of this study is to develop a Practical Module for the Maintenance and Building Services Course and to test the suitability of the developed module. The Sidek model was used as a guide to develop this module. There are two main phases in the Sidek Model, which is the module draft production phase and the second phase is the module draft validation phase. A total of 4 experts have been involved in the validation process of the produced modules. An expert review form using the Gutman scale was used. The collected data were analyzed using Kappa analysis. The findings show that the module produced is suitable for use as a practical learning module for Bachelor of Building Construction Vocational Education students with a high level of agreement between experts. However, the findings also show that there are several improvements that need to be made before the module is ready to be used.